2008
DOI: 10.1182/blood-2007-09-115121
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Gata1 in adult mice results in aplastic crisis, revealing its essential role in steady-state and stress erythropoiesis

Abstract: The transcription factor Gata1 is expressed in several hematopoietic lineages and plays essential roles in normal hematopoietic development during embryonic stages. The lethality of Gata1-null embryos has precluded determination of its role in adult erythropoiesis. Here we have examined the effects of Gata1 loss in adult erythropoiesis using conditional Gata1 knockout mice expressing either interferon-or tamoxifen-inducible Cre recombinase (Mx-Cre and Tx-Cre, respectively). Mx-Cre-mediated Gata1 recombination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
81
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 58 publications
3
81
1
Order By: Relevance
“…GATA1 is expressed in erythroid cells, megakaryocytes, mast cells, eosinophils, and dendritic cells (8,17,30,53) and in Sertoli cells in the testis (12,51). GATA1 has been shown to be essential for erythroid cell differentiation in vivo (6,9,40). Closer examination of Gata1-deficient mice and cells revealed that without GATA1, erythroid cells fail to mature beyond the proerythroblast stage (29,47).…”
mentioning
confidence: 99%
“…GATA1 is expressed in erythroid cells, megakaryocytes, mast cells, eosinophils, and dendritic cells (8,17,30,53) and in Sertoli cells in the testis (12,51). GATA1 has been shown to be essential for erythroid cell differentiation in vivo (6,9,40). Closer examination of Gata1-deficient mice and cells revealed that without GATA1, erythroid cells fail to mature beyond the proerythroblast stage (29,47).…”
mentioning
confidence: 99%
“…7,9 Moreover, ablation of Gata1 expression in adult mice also results in anemia and severe thrombocytopenia from a similar block in erythroid and megakaryocyte maturation as that seen in developmental hematopoiesis. 10 Regulation of the level and spatiotemporal pattern of Gata1 transcription is critical during at least 2 key stages in hematopoiesis for orderly erythroid and megakaryocyte differentiation. In mouse, multipotential progenitor cells initiating Gata1 expression are committed to an erythroid/megakaryocyte (EM) fate.…”
Section: And Malinge Et Al 4 )mentioning
confidence: 99%
“…These results unequivocally indicate that GATA1 is required for erythroid commitment and erythropoiesis in the early stage of hematopoiesis. In addition, well-lobulated mature megakaryocytes that are positive for acetylcholine esterase (AchE) staining are accumulated in the hematopoietic organs of conditional Gata1-null mice, indicating that GATA1 is dispensable from the early stage of megakaryopoiesis and megakaryocyte development to matured polyploid megakaryocytes [56].…”
Section: Leukemogenesis Caused By Gata1 Deficiencymentioning
confidence: 99%
“…Adult Gata1-null mice produced by a conditional deletion of whole coding exons suffer from severe anemia and thrombocytopenia [56]. These mice lack erythroid progenitors, showing a phenotype resembling that of pure red cell aplasia.…”
Section: Leukemogenesis Caused By Gata1 Deficiencymentioning
confidence: 99%